Pengaruh Total Aset Turnover dan Return On Asset Terhadap Nilai Perusahaan - Fassya Firanti Azhar; Nurdin (UNISBA Press, 2023)
Abstract. This study aims to determine and analyze (1) the development of total asset turnover at Digital Bank in 2016-2020; (2) the development of return on assets at Digital Bank in 2016-2020; (3) development of price book value at Digital Bank in 2016-2020; (4) the effect of total asset turnover and return on assets on the price book value of Digital Banks in 2016-2020 either simultaneously or partially. The method used in this research is quantitative with descriptive verification type. The population in this study are Digital Banks registered with the Financial Services Authority (OJK) 2016-2020. The sampling technique used is purposive sampling, with a total sample of 9 digital banks. The analytical technique used in this research is multiple linear regression analysis. The results of the analysis show (1) the development of total asset turnover at Digital Banks in 2016-2020 tends to decrease every year; (2) the development of return on assets at Digital Banks in 2016-2020 tends to decrease every year; (3) the price book value development at Digital Banks in 2016-2020 tends to fluctuate; (4) Simultaneously total asset turnover and return on assets have a significant effect on price book value at Digital Bank in 2016-2020. Partially, total asset turnover has a significant effect on price book value at Digital Bank in 2016-2020, while return on assets has no significant effect on price book value at Digital Bank in 2016-2020. Keywords: Total Asset Turnover, Return on Assets, Firm Value, Digital Bank Abstrak. Penelitian ini bertujuan mengetahui dan menganalisis (1) perkembangan total asset turnover pada Bank Digital tahun 2016-2020; (2) perkembangan return on asset pada Bank Digital tahun 2016-2020; (3) perkembangan price book value pada Bank Digital tahun 2016-2020; (4) pengaruh total asset turnover dan return on asset terhadap price book value pada Bank Digital tahun 2016-2020 baik secara simultan maupun parsial. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan jenis penelitian deskriptif verifikatif. Populasi dalam penelitian ini adalah Bank Digital yang terdaftar di Otoritas Jasa Keuangan (OJK) Tahun 2016-2020. Teknik sampling yang digunakan adalah purposive sampling, dengan jumlah sampel penelitian sebanyak 9 Bank Digital. Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi linear berganda. Hasil analisis menunjukkan (1) perkembangan total asset turnover pada Bank Digital tahun 2016-2020 cenderung mengalami penurunan setiap tahunnya; (2) perkembangan return on asset pada Bank Digital tahun 2016-2020 cenderung mengalami penurunan setiap tahunnya; (3) perkembangan price book value pada Bank Digital tahun 2016-2020 cenderung fluktuatif; (4) secara simultan total asset turnover dan return on asset berpengaruh signifikan terhadap price book value pada Bank Digital tahun 2016-2020. Secara parsial total asset turnover berpengaruh signifikan terhadap price book value pada Bank Digital tahun 2016-2020, sedangkan return on asset tidak berpengaruh signifikan terhadap price book value pada Bank Digital tahun 2016-2020. Kata Kunci: Total Asset Turnover, Return on Asset, Nilai Perusahaan, Bank Digital